Impacts of Rainfall and Temperatures on Socioeconomic and Environmental Sectors in the Communes of Tondikiwindi and Ouallam, Department of Ouallam, Region of Tillaberi, Niger Republic - Mamoudou Idrissa; Boureima Ousmane; Eutache Bonaventure Bokonon Ganta (European Scientific Journal, ESJ, 2018)
The communes of Tondikiwindi and Ouallam in Niger experience changes in rainfall and temperatures like the whole of ahel. This paper focuses on understanding the impacts of these climate parameters on socio-economic and environmental sectors. The methodology is based on calculations of various indices (Lamb, 1982; Tabony, 1977; FAO / UNESCO, 1979) and determination of temperatures within maxima and minima values. With regard to the rainfall evolution, three periods were noted including a long dry period (1968-1989), a relatively wet period (1990-1998), and a period of great variability with an alternation of wet and dry years (1999 -2015). A trend in the South has been noticed in the start and at the end of the rainy season, with a slight decrease in the rainy days. For the temperatures, an increase was registered from 1968 up to date with some slight changes. This is due to the occurrence of the phenomena related to the El Niño or ENSO Southern Oscillation. In terms of impacts, there were several food crises and population migration both inside and outside of the country. On the other hand, the return to a relatively humid phase has led to a change in the Northern limit of cultures, whose corollary is the exacerbation of conflicts between shared natural resources users. This return to an increase in rainfall has also led to major floods that have favored the creation of new permanent or semipermanent pools. Hence, it is necessary to develop a new model of sustainable development for this geographical entity.